Green hydrogen for development: An alternative to natural gas - Collett, K; Silva Ribeiro, C; Hayer, L; Müller, LA; Hirmer, SA (Climate Compatible Growth Programme, 2022)
It is well accepted that hydrogen and its carriers, such as ammonia and methanol, will play a part in our future global energy system. Despite significant uncertainty in future hydrogen demand, one thing is clear: the use of hydrogen is set to increase.